COMPUTATIONAL THINKING: UNPLUGGED ACTIVITIES IN ELEMENTARY SCHOOL - José Raimundo, Anderson; Angélica dos Santos, Claudinea (Journal of Interdisciplinary Debates, 2023)
Technology is present in the world so that its use becomes intuitive. The purpose of the study originated from the perception of people, especially young people who use technology practically all the time, but many of them do not use it to develop. In this case, the need to implement computing teaching in schools increases. The introduction of computing concepts from the early years of basic education gains a lot of importance. Computational thinking instructs people how to think about solving problems through concepts in the field of informatics. The unplugged activity presents great computing concepts, even without the need to use electronic devices, being an effective alternative in teaching. The method used is based on bibliographical reading on the subject and use of resources such as data show, cardboard, markers, cardboard, paper, glue, bond sheets and notebook. The general objective is to present the computer language and its importance by experiencing it in practice through the suggested games. As specific objectives, instigate students to learn by playing, increase interest in subjects such as mathematics, physical education, science, art and the Portuguese language, practice the programming language in known games in an interactive and unplugged way. As expected results are to contribute to computational thinking to become present and worked in schools in order to reframe the school teaching and learning process.